Use and perceptions of digital technology for daily life, physical activity and health information among former cardiac rehabilitation patients in Austria: A cross-sectional survey - Hannah McGowan; Johanna Gutenberg; Veronika Leitner; Kathrin Mühlhauser; Aliz Breda; Michael Fischer; Sebastian Globits; Vincent Grote; David Kiesl; Karl Mayr; Michael Muntean; Andrea Podolsky; et al. (Digital Health, 2023)
Objective Digital health technologies offer great potential to improve access and adherence to cardiovascular disease secondary prevention measures such as regular physical activity (PA). However, the use and perceptions of digital technology (DT) among cardiac rehabilitation (CR) patients are not well understood. The aim of this study was therefore to explore the use of DT in former CR patients’ daily lives, for PA and for health information; and to gain insight into patient perceptions of DT for PA, including barriers, facilitators and requested features. Methods A cross-sectional postal survey was conducted between May 2022 and January 2023. Five Austrian CR centres contacted 500 former patients who had completed a phase 2 CR programme from January 2019 onwards. One-hundred seventeen patients (mean [SD] age, 69 ± 10 years, 22% female) responded. Descriptive and thematic analyses were conducted for closed and open-ended questions, respectively. Results Results indicated high DT usage for communication and informational aspects, and to a large extent also for PA and health information seeking. Main facilitators of DT use for PA were attributed to health and behavioural monitoring. Main barriers were lack of perceived need, lack of interest and poor usability. Most frequently requested features included pulse and blood pressure measurement, step count and compatibility to other devices. Conclusions Patients generally used and perceived DT as beneficial in daily life and for secondary prevention purposes such as PA. The survey identified facilitators, barriers and feature requests, which may inform the design and implementation of digital health interventions for CR patients.